On new multivariate cryptosystems based on hidden Eulerian equations - Ustimenko, V.A. (Доповіді НАН України, 2017)
We propose new multivariate cryptosystems over an n-dimensional free module over the arithmetical ring Zm based
on the idea of hidden discrete logarithm for Z*m. These cryptosystems are based on the hidden Eulerian equations.
If m is a “sufficiently large” product of at least two large primes, then the solution of the equation is hard without
knowledge of the decomposition of m. In the Postquantum Era, one can solve the factorization problem for m and
the discrete logarithm problem for Z*m. However, it does not lead to the straightforward break of such cryptosystem,
because of the parameter is unknown. Some examples of such cryptosystems were already proposed. We define their
modifications and generalizations based on the idea of Eulerian transformations, which allow us to use asymmetric
algorithms based on families of nonlinear multiplicatively injective maps with prescribed polynomial density and
degree bounded by constant. Подано нові криптосистеми від багатьох змінних, визначені на n-вимірному вільному модулі над арифметичним кільцем лишків Zm, що грунтується на ідеї прихованого дискретного логарифма. Такі криптосистеми базуються на прихованих рівняннях Ейлера x^α = a,(α, m) =1. Якщо m є достатньо великим добутком щонайменше двох великих простих чисел, то розв’язок рівняння являє собою важкорозв’язну задачу за умови, що розклад числа m на дільники невідомий. У постквантову епоху задача факторизації розв’язується за поліноміальний час. Цей факт не призводить до безпосереднього зламу такої криптосистеми, тому що параметр α невідомий. Деякі приклади таких криптосистем розглядалися раніше. Запропоновано їх модифікації та узагальнення, які дають можливість використовувати асиметричні алгоритми, що базуються на родинах мультиплікативно ін’єктивних відображень із наперед заданою поліноміальною щільністю та степенем, обмеженим сталою. Представлены новые криптосистемы от многих переменных, определенные на n-мерном свободном модуле над арифметическим кольцом вычетов Zm, основанном на идее скрытого дискретного логарифма. Эти
криптосистемы основываются на скрытых уравнениях Эйлера x^α = a,(α, m) =1. Если m является достаточно большим произведением двух или более больших простых чисел, то решение уравнения составляет
труднорешаемую задачу при условии, что разложение числа m на делители неизвестно. В постквантовую
эру задачу факторизации можно решить за полиномиальное время. Этот факт не приводит к непосредственному взлому такой криптосистемы, так как параметр α неизвестен. Некоторые примеры таких криптосистем рассматривались раньше. Предложены их модификации и обобщения, которые позволяют использовать асимметричные алгоритмы, базирующиеся на семьях мультипликативно инъективных отображений с наперед заданной полиномиальной плотностью и степенью, ограниченной константой.